ТЕРМИНЛЕРДИ ТИЛЛИК АСПЕКТТЕ ИЗЕРТЛЕЎ МӘСЕЛЕСИ - Карибаева, А.У. (SCIENCE and SOCIETY, 2024)
The article analyzes the study of terms in the linguistic aspect, systematization and analysis of formation, effective methods and methods of forming terms in the modern Kazakh language.
Keywords: term; term formation; tracing paper; half tracing paper; borrowings; methods of term formation; term-word combinations